2016
DOI: 10.1007/s40473-016-0066-5
|View full text |Cite
|
Sign up to set email alerts
|

Personalizing the Treatment of Pediatric Obsessive-Compulsive Disorder: Evidence for Predictors and Moderators of Treatment Outcomes

Abstract: Cognitive behavioral therapy (CBT), delivered alone or with a serotonin reuptake inhibitor (SRI), is efficacious for treating pediatric obsessive-compulsive disorder (OCD), but not all youth respond optimally. Research to understand for whom a given intervention is beneficial can inform efforts to personalize treatment or tailor it to specific youths to enhance outcomes. We review studies that examined potential predictors/moderators of response to CBT, medication, and multimodal treatment for pediatric OCD: d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 102 publications
0
6
0
Order By: Relevance
“…While this evidence supports the conclusion of equivalent efficacy of TCBT and CBT at the group level, it is important to acknowledge that the adaptation of CBT for telephone delivery does modify aspects of therapeutic processes such as the therapist's sensitivity to levels of affect which, for certain young people, may diminish or augment their benefits. Identifying pre-treatment characteristics of the child/adolescent, their disorder or environmental context that predict a differential benefit from TCBT or CBT has important implications for treatment assignment and improving the likelihood of therapeutic success [16,17]. Preliminary research on moderators for remotely delivered CBT compared to CBT for adults with social anxiety disorder and depression, for example, has found that higher baseline levels of anxiety or depressive symptoms, and co-morbidity with other emotional disorders, were associated with less favourable outcomes in the remotely delivered CBT group but not in face-to-face CBT [18,19,20].…”
Section: Moderators and Predictors Of Outcomes In Telephone Deliveredmentioning
confidence: 99%
See 1 more Smart Citation
“…While this evidence supports the conclusion of equivalent efficacy of TCBT and CBT at the group level, it is important to acknowledge that the adaptation of CBT for telephone delivery does modify aspects of therapeutic processes such as the therapist's sensitivity to levels of affect which, for certain young people, may diminish or augment their benefits. Identifying pre-treatment characteristics of the child/adolescent, their disorder or environmental context that predict a differential benefit from TCBT or CBT has important implications for treatment assignment and improving the likelihood of therapeutic success [16,17]. Preliminary research on moderators for remotely delivered CBT compared to CBT for adults with social anxiety disorder and depression, for example, has found that higher baseline levels of anxiety or depressive symptoms, and co-morbidity with other emotional disorders, were associated with less favourable outcomes in the remotely delivered CBT group but not in face-to-face CBT [18,19,20].…”
Section: Moderators and Predictors Of Outcomes In Telephone Deliveredmentioning
confidence: 99%
“…A secondary aim of the study was to identify potential predictors of CBT outcome. Knowledge of factors that are associated with an attenuated treatment response can help identify children and adolescents who may benefit from additional or more intense therapy in order to maximise outcomes [16,17] and also assist researchers in specifying factors worth further examining as effect moderators [16]. In a recent systematic review [22] we reported consistent evidence across multiple trials of CBT in children and adolescents with OCD that age, severity of pre-treatment OCD-related impairment, level of co-existing externalising and internalising symptoms, and family accommodation of OCD symptoms were predictors of poorer response to treatment.…”
Section: Moderators and Predictors Of Outcomes In Telephone Deliveredmentioning
confidence: 99%
“…Multiple studies have examined predictors of CBT for pediatric OCD (Turner et al, 2018); however, only OCD symptom severity (Garcia et al, 2010; Ginsburg et al, 2008; Rudy et al, 2014; Torp et al, 2015) and degree of family accommodation (Garcia et al, 2010; Ginsburg et al, 2008; Merlo et al, 2009; Rudy et al, 2014) have been consistently examined. A recent review of the literature (Caporino and Storch, 2016) indicated that symptom severity and family accommodation do not uniformly predict outcome across studies. Other demographic and psychosocial variables have been identified as predictors, such as comorbid internalizing or externalizing disorders (Garcia et al, 2010; Storch et al, 2008; Torp et al, 2015;), age (Torp et al, 2015), functional impairment (Garcia et al, 2010), treatment expectations (Lewin et al, 2011), and gender (Rudy et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Other demographic and psychosocial variables have been identified as predictors, such as comorbid internalizing or externalizing disorders (Garcia et al, 2010; Storch et al, 2008; Torp et al, 2015;), age (Torp et al, 2015), functional impairment (Garcia et al, 2010), treatment expectations (Lewin et al, 2011), and gender (Rudy et al, 2014). Like OCD symptom severity and family accommodation, these psychosocial factors have not been consistently supported (Caporino and Storch, 2016; Turner et al, 2018). The conflicting findings may be attributed to variation in CBT approach (i.e., family vs. individual) or frequency of sessions (i.e., weekly vs. daily intensive; Caporino and Storch, 2016; McGuire et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation